Efektivitas Asosiasi Inokulan Campuran Bakteri Rhizosfer dengan Tanaman Jagung Varietas Srikandi pads Tanah Latosol Lampung - Gandanegara, S.; Sugoro, I.; Slamet, S. (JURNAL BIOLOGI INDONESIA, 2002)
ABSTRACTThe Effectiveness of Rhizospheric Bacteria Mix Inoculant Associated with Maizein Latosol Lampuog Soil. Two greenhouse experiments were carried out to evaluate theeffectiveness of Plant Growth Promoting Rhizobacteria (PGPR) ino-culants on plant growthof maize. In the first experiments, eleven single isolates were screened for associationeffectiveness with maize. Inoculation improved plant perfomance by increasing roots, shootsand total plant dry weight. Five isolates with the increase of plant dry weight ranging from 27-47% over control were then selected for mixed inoculants. In the second experiment, tenmixed inoculants consisted of 3 single isolates were evaluated on plant growth, N plant yield,and N derived from fertilizer and contribution from fixation. The later parameter was.determined by "N method. Three mixed inoculants namely M5, M8, and M9 showed highereffectiveness with the increase of plant weight 27-29% over control. Plant N yield of plantsinoculated with those mixed inoculants were 176-194 mg N/pot as compared to 144 mg Nlpotin control plants. Lower %eIx cess atom % in inoculated plants indicated some Ncontribution from fixation which ranged from 1 5 -2 1 %.Key words : mixed inoculants, % method, maize, latosol